Probing peace journalism: The discursive construction of blackness within the racial democracy of Colombia. (January 2022) - Cortés-Martínez, Carlos A; Thomas, Ryan J
This study examines the discursive construction of blackness in the Colombian men's magazine SoHo, using peace journalism as an evaluative framework. Specifically, it examines 116 feature stories focused on race, published from June 1999 to June 2017. The study found that SoHo did not openly cover racial-structural inequalities, did not contextualize racism, omitted the voices of people of African descent, neglected the race of Black leaders, evaded controversial language, disregarded racial polarization, and presented Black people as disempowered individuals while championing non-Blacks as agents of change. Although SoHo is not a peace journalism project, the magazine's coverage of blackness revealed that avoiding incendiary language – a key tenet of peace journalism – may in fact maintain power dynamics between oppressors and oppressed, as misunderstanding interaction with collaboration does.